Severe Malaria Risk Factors in Lupane District, Zimbabwe. A Retrospective Cohort Study - Batera, Same; Nyamukondiwa, Melisa; Susanna, Dewi; Wispriyono, Bambang (Jurnal Kesehatan Masyarakat, 2024)
Zimbabwe envisions becoming a malaria-free country. However, a malaria resurgence has been reported in some of the elimination districts. This cohort study, guided by the Health Belief Model, aimed to examine risk factors associated with malaria severity in Lupane districts. Using proportionate stratified sampling, the study recruited 1207 individuals, comprising 1056 individuals who acquired malaria locally and 151 individuals who acquired malaria outside Lupane as captured in the DHIS2 electronic malaria-tracker database. The study used IBM SPSS 29.0.2.0(20)] for data analysis and odds ratios (ORs) were used to estimate relative risk (RR; 95% C.I; p0.05). The study revealed relative risk for individuals who had not traveled 29.7 (8.74; 100.0), no Long-Lasting Insecticidal Nets 12.3 (7.02; 21.4), possessed LLINs but not used 7.83 (4.29; 14.3), hosted visitors 6.19 (4.16; 9.22), lived in rural residence 1.94 (1.35; 2.79), slept outdoors during the night 1.93 (1.36; 2.74), and adults 0.22(0.13; 0.36) compared to the corresponding reference groups. As the country continues to fight against malaria, it is critical to address perceived risk factors that can reintroduce the disease and sustain the gains made in malaria elimination districts.